Hak Ex Officio Hakim dan Kesetaraan Gender dalam Perceraian di Pengadilan Agama - Malaka, Zuman (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
Ex officio rights are the authority of judges to decide cases exceeding the demands of the parties, as long as they do not conflict with the law. The implementation of this authority aims to realize justice and guarantee gender equality as mandated by Law Number 1 of 1974, KHI, and Supreme Court regulations. Using normative juridical research methods through analysis of statutory regulations and Surabaya Religious Court Decision Number: 5045/Pdt.G/2024/PA.SBY and 2996/Pdt.G/2024.PA.SBY. The research results show that ex officio rights play role in protecting the vulnerable, especially women, from injustice caused by limited legal understanding regarding the rights of wives after divorce. However, the judge's ex officio rights are not absolute, as they are limited by certain conditions, such as the status of nusyuz or qabla dukhul. Thus, the application of ex officio rights is an important tool in implementing the principles of justice and gender equality in divorce in religious courts